Optimization of patane toraja construction implementation time using critical path method - Sumbung, Putri; Putri, Adila Aisyah; Surahman, Surahman (Enrichment : Journal of Management, 2025)
One of the main challenges in the development of Patane is the lengthy implementation time due to a lack of structured and efficient time planning. This research focuses on streamlining the time needed to construct Patane, a traditional burial site of the Torajan people, by utilizing the Critical Path Method (CPM) in combination with Microsoft Project and QM for Windows software. This study aims to optimize the duration of the Patane development project by using a systematic time management approach. A descriptive quantitative methodology was used to evaluate six interconnected phases of the project, ranging from initial preparation to the final touches. The findings indicated that every activity in the project is part of the critical path, with a total float of zero, leading to an overall project timeline of 84 days. This study underscores the importance of time management tools in culturally focused construction endeavors that encompass intricate social and spiritual aspects. Implementing CPM allows for more organized, effective, and precise project planning and execution, while respecting the cultural values of the Torajan community